METAPHORIC PERCEPTIONS OF PRE-SERVICE TEACHER ONDISTANCE EDUCATION DURING THE COVID-19 PANDEMIC - Kan, Ayşe Ülkü; Özmen, Erhan (My University, 2021)
With the emergence of the coronavirus (Covid-19) pandemic, distance education applications (emergency) have been activated in all educational institutions. This situation has also affected higher education closely. This study aimed to reveal the perceptions of pre-service teachers towards distance education applied during the Covid19 pandemic through metaphors. The research was conducted in a phenomenological design. The study group of the study was determined in accordance with convenience sampling and consisted of 402 teacher candidates who continue their education at a university. Data was collected with forms containing the sentence: “Pandemic period distance education is like ……. ; because…….\". The data were analyzed by content analysis. Participants developed 178 metaphors. These metaphors are grouped into six positive and four negative categories. Considering the metaphors used, distance education was mostly explained with the metaphors of medicine, heroes, water, food, vitamins, and it was emphasized that distance education was necessary and supportive. In addition, it was underlined that there are deficiencies regarding the process and that it should be more efficient.
Keywords: Eğitim; Eğitim Araştırmaları